The Relationship between Hospital Service Quality and Patient Trust is Mediated by Patient Satisfaction in Patient Loyalty at Hospital X - Sekar, Huga; Tan, Pauline H. Pattyranie (Syntax Corporation, 2024)
This study aims to determine the relationship between hospital service quality and patient trust, mediated by patient satisfaction and patient loyalty at the Hospital X. The research method used is quantitative research. The population used in the research were general patients at the Hospital X using a sample size of 162 respondents. The data processing method in this research is structural equation modeling (SEM). The research results show that there are several important findings, such as the quality of hospital services influences patient trust and patient satisfaction, however the quality of hospital services does not influence patient loyalty. Patient trust influences patient satisfaction, patient satisfaction influences patient loyalty as well. Quality of service indirectly influences patient trust through patient satisfaction. Quality of hospital service indirectly influences patient satisfaction through loyalty. Patient trust influences patient satisfaction through patient loyalty. Quality of hospital service. Quality of hospital service influences patient trust through patient satisfaction in patient loyalty.